Teacher Strategies in Overcoming Early Reading Difficulties Among First Grade Students at Ki Bagus Hadikusumo Class, SD UMP - Diyah Mardiyanti; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
Difficulties in early reading during the initial stage of elementary education present a significant challenge, considering that reading ability is a fundamental foundation in learning. The method used in this study is a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. This research aims to describe the results of the strategies implemented by teachers to overcome early reading difficulties among first-grade students at Ki Bagus Hadikusumo Class in UMP Elementary School. The results of the study show that teachers use several strategies, including the phonetic approach, the use of visual and audio learning media, game-based learning, and providing individual assistance to students experiencing difficulties. In addition, parental involvement and collaboration with support teachers also play an important role in supporting the reading learning process. These strategies have proven effective in gradually increasing students' interest and ability in early reading. The study concludes that the active role of teachers in selecting appropriate strategies is crucial to the students’ success in overcoming reading challenges at the early stage of elementary education.